Attitudes of Mental Health Professionals Toward People With Schizophrenia and Major Depression - Nordt, Carlos (Oxford University Press, 2006)
Several studies reveal poor knowledge about mental illness in the general population and stigmatizing attitudes toward people with mental illness. However, it is unknown whether mental health professionals hold fewer stigmatizing attitudes than the general population. A survey was conducted of the attitudes of mental health professionals (n = 1073) and members of the public (n = 1737) toward mental illness and their specific reaction toward a person with and without psychiatric symptoms (“non-case” as a reference category). Psychiatrists had more negative stereotypes than the general population. Mental health professionals accepted restrictions toward people with mental illness 3 times less often than the public. Most professionals were able to recognize cases of schizophrenia and depression, but 1 in 4 psychiatrists and psychologists also considered the non-case as mentally ill. The social distance toward both major depression and the non-case was lower than toward schizophrenia. However, in this regard, there was no difference between professionals and the public. The study concludes that the better knowledge of mental health professionals and their support of individual rights neither entail fewer stereotypes nor enhance the willingness to closely interact with mentally ill people.